Penguatan Institusi Kelompok Tani Hutan Kemasyarakatan Sedyo Makmur Paska Izin Usaha Tebang Kayu di Semanu, Kabupaten Gunungkidul - Rijal Ramdani; Gatot Supangkat Sumidjo; Eko Priyo Purnomo; Kevin Arya Pranaja; Bagaskoro Nur Abu Yogar (Yayasan Pendidikan Penelitian Pengabdian Algero, 2025)
The Community Forestry (HKm) policy gives the Sedyo Makmur Forest Farmer Group (KTH) the right to manage 115 hectares of state forest with the principles of sustainability and community welfare. The programme allows the KTH to plant various trees, such as mango, sengon, cashew and soursop as well as intercropping and logging after 15 years. The Community Forest Utilisation Business Permit (IUP HKm) was granted in 2007 until 2042, with an additional Timber Forest Product Utilisation Business Permit (IUP HHK HKm) in 2019-2024. However, after the expiry of the IUP HHK HKm, the KTH faced several obstacles, including weak managerial and administrative systems, difficulties in establishing cooperation with external parties, and the inability to reforest the 115 Ha of forest that had been cut down. To overcome these problems, two main activities were designed, namely (1) education and mentoring for KTH in organisational governance, administration, and strengthening cooperation networks with various parties, and (2) nursery training and provision of various types of seeds to support reforestation efforts. It is hoped that this programme can strengthen the capacity of KTH in sustainable forest management and improve the welfare of group members.